Appraisal of the Report on SEZ Functioning - Gupta, Deepa; Goyal, Gaurav (Journal of Commerce and Trade, 2009)
Parliamentary Standing Committee Report on the Functioning of Special Economic Zones is a very comprehensive and sensitive document. It is comprehensive because it takes into account consideration of food security, defense, loss of massive tax revenue due to a plethora of exemptions indiscriminately granted both to entrepreneurs and developers, composition of Board of Approvals for SEZ projects, need for replacement of Land Acquisition Act (1894) by a more modern legislation for SEZ, and providing level playing field for industry in Domestic Tariff Area (DTA) and SEZs. It is a sensitive document because it voices the concerns of the farmers, sharecroppers and other co-workers who are the stakeholders in the implementation of SEZ policy.